2018
DOI: 10.1080/23322039.2018.1453452
|View full text |Cite
|
Sign up to set email alerts
|

Does CEO emotional bias affect performance?

Abstract: This article is focused on tackling the issue of the impact of the bank CEO's emotional bias on the Tunisian banks' performance level while accounting for the mediating role of the control systems. In this regard, an empirical study has been set up through a questionnaire undertaken as an appropriately fit data collection method administered to a sample of 100 CEOs of Tunisian banks. Actually, the present research is intended to help in reflecting an original approach, since it serves to highlight the behavior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…the positive role of business practices in firm outcomes (e.g., Cai et al, 2019;McKenzie & Woodruff, 2017;Nguyen & Kim, 2019). The current literature has also stressed the importance of managers' personality traits and competencies and found that the characteristics of managers contribute to variations in the performance and behavior of firms (e.g., Bouzguenda, 2018;Kim, 2020;Soussi & Jarboui, 2018). A natural question arises: whether there exists a connection between managers' personality traits and business practices?…”
Section: Public Interest Statementmentioning
confidence: 98%
See 1 more Smart Citation
“…the positive role of business practices in firm outcomes (e.g., Cai et al, 2019;McKenzie & Woodruff, 2017;Nguyen & Kim, 2019). The current literature has also stressed the importance of managers' personality traits and competencies and found that the characteristics of managers contribute to variations in the performance and behavior of firms (e.g., Bouzguenda, 2018;Kim, 2020;Soussi & Jarboui, 2018). A natural question arises: whether there exists a connection between managers' personality traits and business practices?…”
Section: Public Interest Statementmentioning
confidence: 98%
“…In terms of trait affectivity, an emerging strand of empirical literature has shown that personality traits have a significant role in the effective performance of firms (e.g., ; Soussi & Jarboui, 2018;Tai et al, 2018). An individual with high NA has been found to react to adverse events strongly (Gosserand & Diefendorff, 2005), while trait PA positively relates to enhancing (Nelis et al, 2016).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…This connotes that hubristic managers, coupled with excessive CEO power, could jeopardize corporate performance; however, a strong board could reduce managerial hubris's negative influence on firm performance. Vitanova (2018) find overconfidence to have a positive and significant influence on firm performance Souissi and Jarboui (2018) studied the effect of CEO emotional bias on the performance of Tunisian banks. The study disclosed that optimism and aversion to loss have a significant effect on banks' performance in Tunisia.…”
Section: Literature Review and Development Of Hypothesismentioning
confidence: 99%
“…, 2016; Sirén et al. , 2016; Souissi and Jarboui, 2018). In the related literature, the emotional intelligence (EI) term implies social and emotional skills from an individual's perspective in managing themselves and others, and this concept has emerged to reflect this (Mckenna, 2012).…”
Section: Introductionmentioning
confidence: 99%